Heavy minerals: analysis, results and economic importance - Instituto Geológico Minero y Metalúrgico. Dirección de Geología Regional (2016)
Traditionally, heavy minerals are not the first thing on the mind of explorer geologists worldwide, especially in South America. However, they are of crucial economic importance as non-metallic and metallic raw concentrations. Economic heavy mineral deposits are known as “placer and paleoplacer deposits” and they are mainly located in tropical and sub-tropical countries with high rate of sedimentary denudation and active tectonics since Ordovician time like in Peru.